The Effect of Project Based Learning Model on Students’ Learning Outcomes at SMPN 1 Payakumbuh - Khairunnisa, Kania; Lestari, Tuti; Muttaqiin, Arief; Oktavia, Rani (SEMESTA: Journal of Science Education and Teaching, 2025)
This research is motivated by a learning process that only uses conventional models, so that in class it only focuses on the delivery of material by the teacher. Students are only asked to listen and take notes on the material presented, so that this has an impact on low student learning outcomes. This research aims to determine the effect of the Project Based learning model on the learning outcomes of the 8th grader at SMPN 1 Payakumbuh. This type of this research is quasi experiment using a non-equivalent control group design. This design begins with giving a pretest and ends with giving a posttest to the experimental and control groups. The sampling technique used was purposive sampling. Based on the results of the student response questionnaire to the Project Based learning model, a percentage of 86.45% was found to be in the very good category. Based on the results of hypothesis testing using the t test, a significance value of 3.685 > 2.0003 was obtained, meaning that there is a significant difference in the learning outcomes of students who use the Project Based Learning model and the learning outcomes of students who use conventional learning models. The results of the experimental class N-Gain test were found to be 0.55 in the medium category. It can be concluded that in this research, the Project Based Learning model has a significant influence on the learning outcomes of class VIII students at SMPN 1 Payakumbuh.